PERILAKU MEROKOK PADA PEREMPUAN DI PERKOTAAN (Studi Kasus Mahasiswi Di Kota Pekanbaru) - Kurniafitri, Devi; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problem discussed in this study is to describe how the smoking behavior of women in urban areas with existing case studies student in town Pekanbaru. this study uses accidental sampling. Informants in this study were women’s status as a student in town. Informants are 5 people that students who smoked secretly and openly. Data analysis is Qualitative Descriptive. By filtering the data through Observation and Interviews. The theory used in this research is the theory about the Lifestyle and Gender Theory. From the study it can be concluded that smoking behavior conducted by the student in the city of Pekanbaru came from their own. Smoking behavior conducted by a student in the city Pekanbaru caused by the lack of parental control and strengthened the influence of the environment or peers. The study also illustrates that the student smoking in the city of Pekanbaru classified in light smokers because cigarettes consumed relatively little with consideration of taste, price, and their economic cirucumstances. The study also concluded that students who smoke basically have the knowledge about the negative effects of smoking behavior. They ignore the habit that they do not bring harm to them.Keywords : Behaviour, Smoke, Students